Mechanism of acquisition of chromosomal markers by plasmids in Haemophilus influenzae. - Setlow, J K (1984)
The hybrid plasmid pNov1 readily acquired genetic information from the chromosome of wild-type, but not rec-2, cells. Most of the recombination had taken place 1 h after entrance of the plasmid into the cell, as judged by transformation of rec-2 by lysates made from wild-type cells exposed to pNov1. Measurement of physical transfer from radioactively labeled cellular DNA to plasmids recombining in wild-type cells failed, since there was little more radioactivity in plasmids from such cells than from labeled rec-2 recipients, in which no recombination took place. EcoRI digestion of pNov1 divided the DNA into a 1.7-kilobase-pair fragment containing the novobiocin resistance marker and a 13-kilobase-pair fragment containing all of the original vector and considerable portions homologous to the chromosome. Transformation by the large fragment alone resulted in a plasmid the size of the original pNov1. Our hypothesis to explain the data is that genetic transfer from chromosome to plasmid took place by a copy choice mechanism.